2012
DOI: 10.1007/s10461-012-0192-3
|View full text |Cite
|
Sign up to set email alerts
|

Female Sex Worker Client Behaviors Lead to Condom Breakage: A Prospective Telephone-Based Survey in Bangalore, South India

Abstract: We examined condom breakage rates and predictors of breakage in a prospective telephone-based study of female sex workers (FSWs) in Bangalore, India. We obtained data on 3,257 condom-use sex acts, and breakage occurred in 2.1 % of these. Situational factors, especially those associated with male clients' behaviors, were the most important predictors of breakage, including sexual inexperience, roughness and violence. Breakage was also associated with having vaginal and anal sex at the same encounter and with po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…MSM who initially reported ever or never condom use and moved to consistent condom use have low HIV incidence rate. Second, improper use or product failure because of breakage may have mitigated effect of condom use2021. Third, frequency of condom use relied on self-reporting, and may have been unreliable measure because of the personal nature of the questions posed and potential for desirability22.…”
Section: Discussionmentioning
confidence: 99%
“…MSM who initially reported ever or never condom use and moved to consistent condom use have low HIV incidence rate. Second, improper use or product failure because of breakage may have mitigated effect of condom use2021. Third, frequency of condom use relied on self-reporting, and may have been unreliable measure because of the personal nature of the questions posed and potential for desirability22.…”
Section: Discussionmentioning
confidence: 99%
“…Among studies reporting mean frequency across the whole study sample, the total number of AI and UAI acts ranged from 1.1 to 16.9 (N = 8) and 1.0 to 1.7 (N = 3). The percentage of all intercourse acts that were anal ranged from 2.4 to 15.9% in the six studies that reported it across the whole sample [3,26,[33][34][35][36]. In the sole study which reported it among the subset practising AI [3], 17.0% of intercourse acts were anal.…”
Section: Frequency Of Ai Compared To VImentioning
confidence: 99%
“…We plotted these individual study estimates and produced pooled estimates by recall period (for recall periods with > 3 estimates). Where studies reported condom use as 'always', 'sometimes' or 'never', rather than over a specific recall period, we define answers other than [3, 9, 10, 27-34, 42, 43, 45, 47-155] UAI prevalence only b 5 [22][23][24][25]156] AI frequency 13 [3,9,10,26,[28][29][30][31][32][33][34][35][36] AI prevalence recall period a 'always' as practising UAI or UVI and refer to this recall period as general condom use. All models were fitted using maximum-likelihood random-effects models [16,17] with the procedure 'Metafor' [18] in R version 3.20.1 [19].…”
Section: Prevalence Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Within criminalised environments, physical and sexual violence in the workplace, whether by clients, police, managers, pimps, or predators posing as clients, are among the most ubiquitous and influential determinants of HIV acquisition and transmission risk among FSWs, linked to inconsistent condom use, client condom refusal, condom use failure and breakage,22, 24, 26, 28, 33, 43, 46, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57 and HIV infection. 5, 33, 58, 59, 60, 61, 62 In addition to police abuse as a human rights violation, law enforcement strategies and local policing of sex work, including arrests and incarceration, 26, 38, 61, 63, 64, 65 raids, 64 displacement, 24 and confiscation of condoms or syringes, 64, 66 are key barriers to HIV prevention efforts among FSWs worldwide, which reduces or eliminates the ability to negotiate male condom use 24, 51, 61, 63, 64, 66 and increases HIV prevalence and incidence.…”
Section: Structural Determinants Of Hivmentioning
confidence: 99%